2013
DOI: 10.1016/j.ydbio.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Nerve independent limb induction in axolotls

Abstract: Urodele amphibians can regenerate their limbs. During limb regeneration, dermal fibroblasts are transformed into undifferentiated cells called blastema cells. These dermis-blastema cells show multipotency. Such so-called endogenous reprogramming of cell differentiation is one of the main targets of amphibian limb regeneration studies. It is well recognized that nerve presence controls the initiation of limb regeneration. Accordingly, nerve factors have been sought in amphibian limb regeneration. To investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 47 publications
5
63
0
Order By: Relevance
“…A 2013 study by Makanae et al showed that Gdf5 and FGFs are together capable of inducing blastema growth and limb formation in this model even in the absence of a deviated nerve. 61 Even more recently, Satoh et al have shown that FGF8 and Bmp7 are expressed at the ends of peripheral nerves, and knockdown of these factors inhibits blastema formation in regenerating limbs. 72 These findings reinforce the validity of the AL model as an analog to the amputated limb while demonstrating the necessity of FGFs and BMPs for nerve dependent limb regeneration.…”
Section: Molecular Mechanisms Of Nerve Dependencementioning
confidence: 99%
“…A 2013 study by Makanae et al showed that Gdf5 and FGFs are together capable of inducing blastema growth and limb formation in this model even in the absence of a deviated nerve. 61 Even more recently, Satoh et al have shown that FGF8 and Bmp7 are expressed at the ends of peripheral nerves, and knockdown of these factors inhibits blastema formation in regenerating limbs. 72 These findings reinforce the validity of the AL model as an analog to the amputated limb while demonstrating the necessity of FGFs and BMPs for nerve dependent limb regeneration.…”
Section: Molecular Mechanisms Of Nerve Dependencementioning
confidence: 99%
“…The recent discovery of the involvement of FGF (fibroblast growth factor) and BMP (bone morphogenetic protein) signaling [2426] are encouraging in terms of being able to tease apart the specifics of how this early step in regeneration is controlled. Although an ectopic blastema can be induced to form in response to signaling from the deviated nerve and wound epithelium, it lacks the positional information to make a new limb since the cells recruited from around the wound site all share similar positional codes.…”
Section: Positional Information: the Blueprint For Regenerationmentioning
confidence: 99%
“…This later step is dependent on signals from the nerve that interact with the newly formed wound epithelium to induce formation of a signaling center that recruits mesenchymal cells from the adjacent connective tissue (see [5,21,22]. This step that is dependent on nerve-associated signals in vivo can be regulated by the therapeutic delivery of a defined cocktail of growth factors [23-25]. In so doing, a deviated nerve is no longer required, and the downstream pathways (next steps in the regeneration cascade) leading to blastema formation can be targeted directly.…”
Section: The Alm As An Assay For Signaling That Is Required For Endogmentioning
confidence: 99%
“…human recombinant growth factors induce ectopic blastema formation in the axolotl [23,25]). The lack of a regenerative response in humans may be a consequence of a failure to produce the necessary signals at the right time or place, but it is unlikely that there is a problem in the underlying pathways themselves.…”
Section: Mammalian Signaling Molecules That Induce a Regeneration Resmentioning
confidence: 99%